2021
DOI: 10.1007/s11695-020-05166-z
|View full text |Cite
|
Sign up to set email alerts
|

Body Image Disturbances and Weight Bias After Obesity Surgery: Semantic and Visual Evaluation in a Controlled Study, Findings from the BodyTalk Project

Abstract: Purpose Body image has a significant impact on the outcome of obesity surgery. This study aims to perform a semantic evaluation of body shapes in obesity surgery patients and a group of controls. Materials and Methods Thirty-four obesity surgery (OS) subjects, stable after weight loss (average 48.03 ± 18.60 kg), and 35 overweight/obese controls (MC), were enrolled in this study. Body dissatisfaction, self-esteem, and body perception were evaluated with sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 55 publications
0
21
1
Order By: Relevance
“…For example, the psychological effects of weight loss on patients with severe obesity are considered only partially positive because various social or interpersonal difficulties can result in excess skin excess that remains after bodyweight reduction [ 7 , 18 ]. After a person undergoes bariatric surgery, social and psychological support is sometimes suggested for improving their social interactions and psychological status and reducing the risk of relapse due to excess skin and body image modification [ 1 , 19 , 23 , 27 ]. Besides, cognitive aspects could require specific interventions; for example, an individual’s interpretation of interpersonal interactions, whereby they perceive stigma and aloneness, could stem from their childhood and impact the treatment outcome [ 21 , 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the psychological effects of weight loss on patients with severe obesity are considered only partially positive because various social or interpersonal difficulties can result in excess skin excess that remains after bodyweight reduction [ 7 , 18 ]. After a person undergoes bariatric surgery, social and psychological support is sometimes suggested for improving their social interactions and psychological status and reducing the risk of relapse due to excess skin and body image modification [ 1 , 19 , 23 , 27 ]. Besides, cognitive aspects could require specific interventions; for example, an individual’s interpretation of interpersonal interactions, whereby they perceive stigma and aloneness, could stem from their childhood and impact the treatment outcome [ 21 , 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…The role of weight bias in concerns over body image in bariatric surgery patients could jeopardise the results of their treatment. Obese people tend to percieve their weight incorrectly, even after bariatric surgery, patients seem unable to identify changes in their body image after massive weight loss [ 47 ]. Social support could positively influence body image perception and interpersonal body comparisons after bariatric surgery, although additional studies should be carried out.…”
Section: Discussionmentioning
confidence: 99%
“…Body dissatisfaction depends on BMI ( 43 ), but weight loss after surgery is not sufficient to reduce psychological stress, which is associated with body image satisfaction and increased emotional eating ( 31 ). Meneguzzo et al showed that patients who underwent bariatric surgery encountered more difficulties after undergoing surgery in assessing their body size with respect to BMI than overweight and obese people who did not undergo surgery ( 44 ). Given the validity of the body image construct and bulimic behavior, we thought it would be interesting to establish the predictive role of multidimensional body image in bulimic-type eating behavior among individuals scheduled for the surgical treatment of obesity.…”
Section: Discussionmentioning
confidence: 99%
“…The identification of body image disorders and bulimic eating behaviors enables the application of specialized therapeutic procedures in preparation of a patient for bariatric surgery. The inclusion of the perspective of experiencing the body and its relationship with self-regulatory mechanisms related to eating is a valuable direction in psychological interactions, both before and after bariatric surgery ( 44 , 57 , 58 ). This may lead to better results in the surgical treatment of obesity, understood as the number of kilograms reduced in the long term, a reduction in unhealthy behaviors, and an improvement in the overall quality of life ( 59 ).…”
Section: Discussionmentioning
confidence: 99%